Enhancing English proficiency enjoyably: Improving language skills through watching engaging and educational English movies - Ni Wayan Sadiyani; Ni Wayan Ratna Wulandari; Edona Jahiu; Nadia Idri; Rodolfo P. Dizon Jr; Md. Kamrul Hasan (Journal of Language and Pragmatics Studies, 2025)
The purpose of this paper is to explain the benefits of watching English movies as an effective way to improve language skills. This method offers learners a practical and enjoyable way to enhance their English proficiency, including listening, speaking, vocabulary, and pronunciation. Watching movies allows learners to experience real conversations, different accents, and the correct use of English in daily life, making learning more meaningful and engaging. Using subtitles can help learners connect spoken words with their written forms. Beginners can start with subtitles in their native language and gradually switch to English subtitles to improve grammar and vocabulary. Movies with different accents, like American, British, or Australian, also help learners understand various ways of speaking English. Research supports the benefits of watching English movies for language learning. Studies show that movies help learners understand words in context, improve listening skills, and learn proper pronunciation. Repeating scenes, writing down new vocabulary, and practicing speaking based on movies enhance retention and usage. Moreover, movies introduce learners to different cultures, making learning more interesting and informative. This method is suitable for learners at all levels. Beginners can watch simple movies like animations, while advanced learners can explore movies with more complex dialogues. Rewatching movies helps learners notice new details, such as sentence structures and pronunciation, that they might have missed before. Discussing movies with others is also a fun way to practice speaking and critical thinking. In conclusion, watching English movies combines education and entertainment, providing learners with an enjoyable way to improve their English skills. It motivates learners, helps them understand authentic language use, and enriches their cultural knowledge, making it a valuable tool for language learning.